How to assess multimorbidity: a systematic review - Yao, Li; Li, Qiaoxing; Liu, Yan; Li, Qinqin; Wang, Tingrui; Zhou, Zihan; Yin, Jiajia (Frontiers in Public Health, 2025)
ObjectiveTo comprehensively and systematically collect the methods used in the evaluation of patients with multiple chronic diseases both domestically and internationally, summarize and analyze the purpose, characteristics and validity of their initial development, and provide reference for health managers to choose appropriate evaluation methods for multiple chronic diseases.MethodsAnalysis of the literature was based on searches conducted across eight electronic databases, including PubMed, EMBASE, Web of Science Core Collection, Scopus, Cochrane Library, CNKI, Wan Fang Database, and the Chinese Biomedical Literature Database (CBM). The initial search was completed on January 8, 2024, and the most recent update was conducted on December 10, 2024, with no restriction on the date of publication. The search process adhered to the 2020 PRISMA guidelines for systematic review.Results54 literatures meeting the criteria were included, involving 54 evaluation methods of multiple chronic diseases. It can be divided into four categories: (1) assessment based on equal weight of disease count and disease severity; (2) based on physiological and psychological health status assessment; (3) evaluation based on drug use; (4) natural language processing evaluation system.ConclusionAttention should be paid to the assessment of patients with multiple chronic diseases, and standardized and unified assessment methods should be developed in the future to expand the coverage of diseases and deepen the depth of assessment, so as to provide more comprehensive and accurate health management for the growing number of patients with multiple chronic diseases.Without patient or public contributionThis systematic review is primarily based on the comprehensive analysis of published literature and did not involve new data collection or direct participation of patients, hence there was no direct contribution from patients or the public.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42024530474.